ANALISIS TINGKAT KEPUASAN PETANI TAMANU TERHADAP POLA KEMITRAAN DENGAN PT SINERGI NATURAL NUSANTARA DI KEBUMEN - Suciati, Devia; Harli, Nurlina (Agros Journal of Agriculture Science, 2024)
Various efforts have been made by the government to increase farmers' income in order to prevent disparities by creating a self-sustaining economic system, one of which is by developing agricultural businesses through partnership models. This research aims to analyze the level of satisfaction among tamanu farmers regarding the partnership model with PT Sinergi Natural Nusantara. The methods used are CSI (Customer Satisfaction Index) and IPA (Importance Performance Analysis). Farmers feel satisfied with their partnership with PT Sinergi Natural Nusantara, as indicated by a CSI score of 77.4%. PT Sinergi Natural Nusantara can evaluate the attributes that need improvement in order to enhance the quality of the company's services